Identification, characterization, and antibacterial studies of furobenzopyrans from Ammi visnaga - Rajendra Moorthy Rajendran, Brindha Devi Parthiban (Journal of Applied Pharmaceutical Science, 2023)
In this study, we have reported the identification, characterization, and antibacterial effect of furobenzopyrans (FBP) from Ammi visnaga. The dried fruits of A. visnaga plant material were investigated using aqueous and organic solvent [methanol, tetrahydrofuran (THF extract), and chloroform] extractions. Amongst, the THF extract showed significantly higher antibacterial activity against Escherichia coli than the other solvent extracts (p < 0.05). Then, the THF extract was investigated using gas chromatography coupled with a mass spectrometer (MS) and mass spectral database analysis for the identification of the compounds. From this analysis, almost 26 compounds were seen, and 2 compounds were found to be FBP derivatives. The THF extract was analyzed using a C18-solid phase purification step for isolating the FBP and then extracted using THF (THF fraction). The obtained THF fraction was subjected to high-performance liquid chromatography (HPLC), MS, and Fourier transform infrared (FTIR) analysis for identifying and characterizing the FBP. The HPLC analysis showed that the FBP eluted at around 21 minutes, which had a purity of 91%. The FTIR analysis showed transmittance at 1054, 2958, 2878, and 923 cm−1 suggesting the presence of methoxy, aromatic ring, and ketone functional groups in the THF fraction. The fraction was also subjected to mass analysis and the mass was found to be m/z 246.053. On observing the fragment ions, major ions were seen at m/z 246 and 231, which confirms the identity of 5H-Furo[3,2-g][1]benzopyran-5-one, 4,9-dimethoxy. Then, the effect of this compound on E. coli growth was studied at various concentrations, ranging between 0.16 and 20 μg/μl. Complete inhibition was observed for groups treated with ≥10 μg/μl, whereas slow growth was observed with groups treated with
Keywords: Ammi visnaga, antibacterial agents, furobenzopyrans, extraction, medicinal plants